Zespół kafli gotyckich z Ujazdu koło Tomaszowa Mazowieckiego - Garas, Marta (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
The article describes a find of Gothic tiles found in the course of archaeological-architectonic research in the area of a residence in Ujazd near Tomaszów Mazowiecki. The most important owners of the town, who considerably influenced the appearance of the castle, and then the palace were Piotr Strykowski, Piotr Dunin, Kacper Denhoff and the Ostrowski family. Material reflection of the complexes splendor were movable artifacts obtained during archaeological-architectonic research in the years 2002–2004. The Gothic tiles, which constitute about 75% of a rich collection consisting of over 1600 fragments were characteristic of the wealth of decorative motifs, which were divided into thematic groups. Among them, coat of arms representations, genre, sacral, court, architectonic renderings and illustrations of fauna and flora were distinguished. Most frequent were tiles with images of coats of arms – presented in three graphic manners of simple narration. Specimens with more developed stylistics were less numerous (representation of Doliwa coat of arms with attributes of the metropolitan bishop of Gniezno may be an example). Except the national emblem, White Eagle, all the other emblems represented on tiles of Ujazd were mentioned in “Klejnoty”, authorship of which is ascribed to Jan Długosz. Except tiles with images of coats of arms, specimens on which scenes of court and knight’s themes were distinguished – for example a scene with Saint George fighting the dragon, and probably amusement motifs, such as a representation of a march of musicians with a bear. The collection also included tiles with representations of moralizing implications, which comprised a fox watching for geese. What is also interesting is examples of images of various creatures, which are central motifs on tiles’ faces. First of them was a hybrid with human face and six limbs, the other – commonly known mermaid. Such creatures also include a tiger – this animal, although existing in a real world, in the Middle Ages was represented as a fantastic hybrid. Moreover, architectonic motifs among which most interesting is a representation of the castle enclosed in schematic coat of arms were distinguished. The described collection was compared to collections coming from royal, prince’s and bishop’s residences from the area of Great Poland Province.